Eksistensi Kelompok Kerja Guru Dalam Penguatan Kompetensi Profesional Guru Quran Hadits Madrasah Ibtidaiyah Di Kota Banda Aceh - Kamaliah, Kamaliah (Institut Agama Islam Daruttaqwa Gresik, 2023)
The purpose of this study was to determine the planning, implementation and evaluation of the KKG in strengthening the professional competence of Quran Hadith teachers at Madrasah Ibtidaiyah in Banda Aceh City. This research was conducted with a field study using a qualitative descriptive method. The research subjects consisted of chairman of the KKG, five head master, five Qur'an Hadith teachers, and two madrasa supervisors. Data collection techniques were carried out through interviews, observation and documentation. The results showed that the planning of the KKG Quran Hadith Madrasah Ibtidaiyah program was carried out together with KKG administrators and members and involved supervisors and general chairmen of the Banda Aceh City KKG. The content in planning include educational policies, routine programs and supporting programs. The implementation of the program is adjusted to the needs and budget, routine activities reach the target but development activities have not been carried out as expected. The infrastructure in KKG activities belongs to each participant. Funding for activities comes from members' self-help, and in 2021 KKG will receive assistance from Block Grant funds. Teacher participation in the KKG is greater when receiving Block Grant funding in 2021 compared to not receiving financial assistance. The resource persons for the activities came from members of the KKG, Fasda/Fasprov, Head of the Ministry of Religion, Head of Madrasah Education, Madrasah Supervisors, and other relevant resource persons, with the place of activity at the madrasa which was mutually agreed upon. As for efforts to increase teacher professional competence in self-development activities and collective activities, scientific publications and innovative works are still very low. Evaluation of the Quran Hadith KKG was carried out by the madrasa supervisor through a report submitted by the KKG to the Ministry of Religion of Banda Aceh City at the end of the year. Evaluation of teachers who are members of the KKG is carried out by the head of the madrasah. In general, after participating in the KKG activities, teachers already know more about the foundations of education, are able to develop teaching materials, are able to prepare teaching programs, and evaluate learning well. However, the teacher's ability to carry out scientific publications and innovative works is still very low.